Identification of a 5-lncRNA-Based Signature for Immune Characteristics and Prognosis of Lung Squamous Cell Carcinoma and Verification of the Function of lncRNA SPATA41 - Huan, Sheng; Chen, Miao; Sun, Sumin; Zhong, Yanling; Chen, Yu; Ji, Yihao; Yin, Guoping (Frontiers in Genetics, 2022)
Abstract Lung squamous cell carcinoma (LUSC) is one of the most lethal cancers worldwide. Traditional tumor-node-metastasis (TNM) staging system has much insufficiency in predicting immune characteristics, overall survival (OS) and prognosis of LUSC. LncRNA is currently found involved in tumor development and effectively predict tumor prognosis. We screened potential tumor-related lncRNAs for immune characteristics and constructed a nomogram combining lncRNA and traditional clinical indicators for prognosis prediction. We obtained the large-scale gene expression profiles of samples from 492 LUSC patients in The Cancer Genome Atlas database. SPATA41, AL034550.2, AP003721.2, AC106786.1 and AC078889.1 were finally screened to construct a 5-lncRNA based signature. The riskscore of the signature devided patients into subgroup of high-risk and low-risk with significant difference in OS. The area under the curve (AUC) of them reached more than 0.70 in 1, 3 and 5 years. In addition, compared with the high-risk subgroup, the low-risk subgroup exhibited a remarkably favorable prognosis and TME score, along with a higher immune infiltration score and lower TIDE score. The signature also showed a significant relation with chemotherapy response, especially in cisplatin, vinorelbine and paclitaxel. Importantly, the nomogram we constructed had a good reliability with the assessment of calibration chart and consistency index (c-index). GO and KEGG enrichment analysis indicated that co-expression mRNAs of the 5 lncRNAs were mainly focused on RNA splicing, DNA replication and protein serine/threonine kinase activity. Functional assays demonstrated that SPATA41, one of the five OS-related lncRNAs, regulated invasion, migration, proliferation and programmed death in vitro. In summary, our 5-lncRNA based signature has a good performance in predicting immune characteristics and prognosis of LUSC patients.